2020
DOI: 10.15283/ijsc19155
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Epithelial Cells Affect the Functions of Neutrophils

Abstract: Background and Objectives: As a stem cell group, Human amniotic epithelial cells (HAECs) have numerous advantages over their embryonic and adult counterparts for therapeutic utility. They are closer to clinical applications compared to other stem cell types. Additionally, the anti-inflammatory and immunoregulatory properties of HAECs toward several immune cells have been shown previously. Nevertheless, despite the ever-increasing importance of neutrophils in the immune and non-immune processes, a few studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…Moreover, hAESCs exert multiple immunosuppressive activities via inhibiting the cytotoxicity of NK cells and monocytes and promoting the induction and maturation of Treg cells [ 131 , 132 ]. Recently, researchers found that hAESCs can improve the phagocytic ability of neutrophils while reducing their oxidative burst capacity, thereby protecting the fetus from both microbial infections and oxidative stress and the consequent inflammation [ 133 ].…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
“…Moreover, hAESCs exert multiple immunosuppressive activities via inhibiting the cytotoxicity of NK cells and monocytes and promoting the induction and maturation of Treg cells [ 131 , 132 ]. Recently, researchers found that hAESCs can improve the phagocytic ability of neutrophils while reducing their oxidative burst capacity, thereby protecting the fetus from both microbial infections and oxidative stress and the consequent inflammation [ 133 ].…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
“…Moreover, monocytes secreted less TNF-α and IL-6 (Li et al, 2015;Tan et al, 2015). AM improved the phagocytosis of neutrophils, but at the same time, decreased their oxidative burst capacity and neutrophil extracellular traps (Navas et al, 2018;Alipour et al, 2020). Another immunomodulatory property of hAECs was observed through the trogocytosis process, where cell-to-cell transfer of human leukocyte antigen G (HLA-G) from hAECs to effector T cells was observed, which may account for the acquisition of a regulatory T cell (Treg) phenotype independent of FoxP3 transcription.…”
Section: Properties Of the Amniotic Membrane Immunomodulatory Functionmentioning
confidence: 99%
“…It is reported that hAECs have immunomodulatory impacts on adaptive and innate immune systems [17,88,89]. They exert suppressive effects on the activations of natural killer (NK) and CD4+ T cells, migrations of neutrophil and macrophage, secretions of pro-inflammatory cytokines of CD4+ T cells, and proliferation of B cells [23,61,90,91]. These impacts are primarily mediated through the productions of immunoregulatory mediators, such as IL-4, PG-E2, and transforming growth factor-beta (TGF-β), which may participate in the increase of Tregs and Th2 cells, inhibition of pathogenic T-cell reactions, and protection of the peripheral naive CD4+ T-cell source [61,63,[92][93][94][95].…”
Section: Human Amniotic Epithelial Cells (Haecs)mentioning
confidence: 99%